Positive Sufism and the Construction of Social Ethics in Contemporary Muslim Society - Jamaldi Jamaldi; Pismawenzi Pismawenzi; Endrika Widdia Putri; Yahya Ibrahim; Rahmad Tri Hadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Current perspectives on Sufism also take into account its social and ethical aspects, but existing studies about it are still mainly restricted to analysis of neo-Sufism, social Sufism, or practical mysticism of individuals without developing any conceptual model for “positive Sufism.” This current study is an attempt to develop the concept of positive Sufism as a modern ethical-spiritual paradigm as well as discuss its applicability to social ethics in the contemporary Muslim community. In this research project, a qualitative library research method was used through an exploratory and analytic approach. Information was gathered from books, journals, and other academic sources related to Sufism, Islamic ethics, and Islamic thought. It is concluded that positive Sufism is a contextual reinterpretation of Sufi spirituality involving spiritual awareness, moral reform, rational reflection, and social commitment. Contrary to conventional views of Sufism as being otherworldly and inactive in social matters, positive Sufism makes the world itself a site for the realization of divine qualities through justice, mercy, accountability, tolerance, and social activity. Indeed, from the theoretical perspective, positive Sufism makes a contribution by mediating the dichotomy between spirituality and social ethics in modern Islamic thought. In this way, positive Sufism is not only an individual religious practice but also an ethical-spiritual tradition that can address the issues of modernity in the Muslim world such as materialism and individualism.